(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to know the level of preparedness of Grade 12 General Academic Strand students on Hybrid Learning Modality in terms of Attendance, Examination, Quizzes, and Recitation. This study indicates that many grade 12 GAS students of Bestlink College of the Philippines are preparing in both online and face-to-face classes despite low internet connection and remote areas. This research recommended that they should give students specialized instruction and resources to support the growth of their digital literacy and assist students in navigating the demands and expectations of hybrid learning by providing clear, consistent communication and guidance.